Word precursors in the Zhyrau poetic culture (Eurasian Journal of Philology Science and Education, 2016)
Poetry of Kazakh and nogaylin zhyrau has historically and mentally conditioned holistic nature, it is rooted in the traditional melos and ethos, closely linked with customs and rituals of the ancient semi-nomadic societies of nomad warriors, with its military traditions, principles, relationships, including sacred beliefs, representations and verbal magic. Without all of this complex it is difficult to understand features of poetry of Kazakh zhyrau, in particular, formulaicity, hardness of canonical forms, stereotypes of metaphors and symbols, historical semantics of markers, concepts, fetishes, urans, totems, vocabulary with metasemantic meaning, ethnonyms and anthroponyms, realities, terms of ethnographic and mythological significance, which are abundant in the poetry. In the analysis of the poetry you should take into account not only the historical background, but also a close connection with the traditions of the poetry of Turkic heroic epic, having a long history and its canonical principles. Laws and attitudes of Turkic heroic epic penetrate deeply into the structure of poetry of Kazakh zhyrau and largely determine its organization and function of vocabulary and stylistics. In this connection you should take into account the characteristics of the traditional Kazakh rhythm structure of alliterative verse, which are largely reproduced in the structure of poetry of zhyrau.
Keywords: epic; heroic song; autopoiesis; fractal; melos; etho; hyperbole; metaphor; concept.